From nanomelting to nanobeads: nanostructured SbxBi1−x alloys anchored in three-dimensional carbon frameworks as a high-performance anode for potassium-ion batteries. Issue 47 (21st November 2019) - He, Xiao-Dong; Liao, Jia-Ying; Wang, Shuo; Wang, Jun-Ru; Liu, Ze-Hua; Ding, Xiang; Hu, Qiao; Wen, Zhao-Yin; Chen, Chun-Hua
Abstract : A modified Pechini sol–gel method was developed to synthesize three-dimensional pomegranate-like Sb x Bi1− x @C composites as anode materials for advanced potassium-ion batteries. Abstract : Potassium-ion batteries (KIBs) are considered a favorable candidate for large-scale electric energy storage system applications owing to the abundance and low-cost of potassium resources. Herein, a series of three-dimensional pomegranate-like Sb x Bi1− x @C composites are fabricated by a modified Pechini sol–gel method. As an anode for KIBs, the Sb0.5 Bi0.5 @C composite exhibits the optimal performance (382 mA h g −1 at 0.05 A g −1 ). More importantly, the synergistic effects in the binary alloy bring a promising long-term cycle life (83% capacity retention after 400 cycles) for Sb0.5 Bi0.5 @C. The ex situ X-ray diffraction results reveal the K storage mechanism of this material, which is Sb0.5 Bi0.5 ↔ KSb0.5 Bi0.5 ↔ K3 Sb0.5 Bi0.5 during discharge and charge processes. In addition, a full cell constructed by coupling Sb0.5 Bi0.5 @C with a Prussian blue cathode delivers outstanding electrochemical performance.